Development of a conceptual model for risk-based quality management system. (3rd April 2019) - Samani, M.A.; Ismail, N.; Leman, Z.; Zulkifli, N.
Abstract : In this study, it is shown the attitudes and approaches behind the two important function-specific management system standards developed by International Organization for Standardization, namely quality management system (QMS) based on ISO 9001:2008 and risk management system (RMS) based on ISO 31000:2009, are largely similar and complementary. Also, both these management systems (MSs) are essential elements of organisational performance management system. Thus, as the key result, integration of the above MSs is suggested and a conceptual model to support this integration is introduced. The integration model is called risk-based quality management system. The main driver for such integration are: to reduce the number of MSs in an organisation and hence to decrease the number of resources employed and to enhance the organisation performance as both RMS and QMS are two sides of the same coin. The proposed risk-based conceptual model is built upon a review and analysis of authoritative journal papers in the field which shows there are some gaps. The risk-based conceptual model is developed on the basis of total quality integration model and the process approach. Finally, to implement the proposed model, an implementation methodology is suggested.